2016
DOI: 10.1002/fsn3.406
|View full text |Cite
|
Sign up to set email alerts
|

The rehydration behavior of microwave‐dried amaranth (Amaranthus dubius) leaves

Abstract: The effect of temperature (35, 50, and 60°C) on the rehydration behavior of microwave‐dried amaranth (Amaranthus dubius) leaves was investigated. Leaves were dried at 700 W power level before rehydrating in water. The higher the rehydration temperature, the higher the equilibrium moisture content of the leaves, although the effect was not statistically significant. The increase in rehydration ratio was significant only as temperature increased from 50 to 60°C. The process was adequately described by the Peleg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…An increase in RR was noted with increasing rehydration temperature from 20 to 80 °C, this may be supported by the fact that with a rise in temperature, moisture also penetrated to the dried product at a higher rate. Balasbramanian et al [27], Doymaz et al [23] and Mujaffar et al [28] found similar observation for rehydration of dried betel leaves, mushroom slices, and amaranth leaves. For FD pineapple slices at 80 °C a maximum value of 0.969 was reported in terms of CR whereas the minimum value…”
Section: Resultsmentioning
confidence: 60%
“…An increase in RR was noted with increasing rehydration temperature from 20 to 80 °C, this may be supported by the fact that with a rise in temperature, moisture also penetrated to the dried product at a higher rate. Balasbramanian et al [27], Doymaz et al [23] and Mujaffar et al [28] found similar observation for rehydration of dried betel leaves, mushroom slices, and amaranth leaves. For FD pineapple slices at 80 °C a maximum value of 0.969 was reported in terms of CR whereas the minimum value…”
Section: Resultsmentioning
confidence: 60%
“…The application of rehydration to dried samples generally resulted in a higher decrease in b* and increase in a* as compared to dried ones for all varieties due to leaching of color pigments to the hydrating solution (Mujaffar & Lee Loy, 2017) and completion of browning reactions occurred in drying process (Zhang & Chen, 2006), respectively.…”
Section: Colormentioning
confidence: 97%
“…Published literature on the rate of respiration (r CO2 ) of amaranth (whole plant and leaves) consisted of three studies that reported respiration at storage temperatures ranging from 5 to 42°C ( Thammawong et al, 2019). To convert published values to similar units (g • kg -1 • h -1 ) on a FW basis, leaf area, weight, and moisture content of amaranth (Jangde et al, 2018;Mujaffar and Loy, 2016;Singh et al, 2014) were used.…”
Section: Methodsmentioning
confidence: 99%